1994
DOI: 10.1038/bjc.1994.436
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of inoperable hepatocellular carcinoma with intrahepatic arterial yttrium-90 microspheres: a phase I and II study

Abstract: SmumuaryEighteen patients with inoperable hepatocellular carcinoma (HCC) were treated with intrahepatic arterial yttrium-90 microspheres. All these patients showed a lung shunting below 15% and a tumour-tonormal ratio higher than 2 as determined by diagnostic technetium-99m macroaggregated albumin (Tc-MAA) gamma scintigraphy. The treatment was given through an arterial port placed during laparotomy. The radiation doses to the liver and tumour were determined intraoperatively with a beta probe and liquid scinti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
113
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(116 citation statements)
references
References 25 publications
(20 reference statements)
2
113
0
1
Order By: Relevance
“…In particular, dose escalation in 10 patients showed that up to 138 Gy to the nontumorous liver by SIR treatment did not cause clinical radiation hepatitis (31). Moreover, 70 Gy by SIR treatment to the nontumorous part of the liver is tolerable in cirrhosis (32). Biopsies in 4 patients receiving up to 75 Gy by SIR treatment showed a minimal histologic effect in the healthy liver (31).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, dose escalation in 10 patients showed that up to 138 Gy to the nontumorous liver by SIR treatment did not cause clinical radiation hepatitis (31). Moreover, 70 Gy by SIR treatment to the nontumorous part of the liver is tolerable in cirrhosis (32). Biopsies in 4 patients receiving up to 75 Gy by SIR treatment showed a minimal histologic effect in the healthy liver (31).…”
Section: Discussionmentioning
confidence: 99%
“…This results in delivering doses of ionizing radiation above 120 Gy to the tumor compartment without causing intolerable toxicity to the normal liver (60,61). RE demonstrated a close relation between delivered dose and tumor response (62). The dose of the radioactive microspheres is adapted to the lung shunting fraction, if present, and assessed before RE by scintigram obtained after intra-arterial infusion of 99 mTc-macroaggregated albumin (highest tolerable dose of the lung %30 Gy).…”
Section: Radioembolizationmentioning
confidence: 99%
“…Various studies have found an association between tumor absorbed radiation doses, tumor response and overall survival. [39,40,41,42] It can, therefore, be expected that improved tumor selectivity of radioactive microsphere distribution will positively affect patient outcome after RE.…”
Section: Author (Year)mentioning
confidence: 99%